Analisis Pengaruh Kebijakan Hutang Terhadap Kinerja Keuangan Perusahaan - Octa Dwi Yanti; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of debt policy on the financial performance of manufacturing companies in the food and beverages sector from 2019 to 2020 which are listed on the Indonesia Stock Exchange. Debt policy is proxied by short term debt (STD), long term debt (LTD), and total debt (TD), while financial performance is used by return on equity (ROE). The method in qualitative research in determining the sample uses a purposive sampling method. The sample used was 9 companies. The analysis technique used is multiple linear regression. Based on the research results, it shows that the table shows that the results of the t test (partial) are that the short term debt variable is 0.456 > 0.05 so that H0 is accepted and Ha is rejected, which means that this independent variable partially has no significant effect on the Return on Equity variable. The long term debt variable is 0.019 < 0.05 so that H0 is rejected and HA is accepted, which means that this independent variable partially has a significant effect on the Return on Equity variable, while the total debt variable is 0.002 < 0.05 so that H0 is rejected and Ha is accepted, which means This means that this independent variable partially has a significant effect on the Return on Equity variable. Companies included in the Food and Beverages sector manufacturing company group listed on the Indonesia Stock Exchange (BEI) for the 2019-2020 period. Potential investors who want to invest must consider the company's existing debt policy. You need to pay attention to the debt strategy used, because long-term debt will affect the company's financial performance.